Gross Morphometrical Study on the Brain of Fowl (Gallus domesticus) - Gupta, Sunil K; Haswitha, Sabbineni; Kaur, Amandeep (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Morphological study was conducted on the brain of nine fowl aged from 2 to 6 months. The pear-shaped brain lodged in the cranial  cavity was 3.34 ± 0.08 g in weight, with a length of 26.69±0.40 mm and width of 20.60 ± 0.17 mm. It consisted of cerebral hemispheres,  pineal body, optic lobes, and cerebellum when viewed from the dorsal surface. On ventral surface, from cranial to caudal end it had  olfactory bulbs, orbital faces of the cerebral hemispheres, optic chiasma, optic tract, optic lobes, hypophysis cerebri, midbrain (cerebral  peduncles), pons and medulla oblongata, which was continued into the spinal cord. Olfactory bulbs present on the tapered cranial end  of cerebral hemisphere were so closely attached with each other that were giving the appearance as a single structure. The cerebral  hemispheres were obtuse triangular and devoid of gyrus and sulci. The cerebellum was located behind the transverse sulcus and had  gyri and sulci. It was round structure resembling a curled worm and was 11.80±0.25 mm in length and 8.53±0.21 mm in width.
Keywords: Avian anatomy; Avian brain; Fowl; Gross morphometry